Approach to patients with pseudo-Cushing's states. Issue 1 (January 2020) - Scaroni, Carla; Albiger, Nora M; Palmieri, Serena; Iacuaniello, Davide; Graziadio, Chiara; Damiani, Luca; Zilio, Marialuisa; Stigliano, Antonio; Colao, Annamaria; Pivonello, Rosario; ,
Abstract : The distinction between pseudo-Cushing's states (PCS) and Cushing's syndrome (CS) poses a significant clinical challenge even for expert endocrinologists. A patient's clinical history can sometimes help to distinguish between them (as in the case of alcoholic individuals), but the overlap in clinical and laboratory findings makes it difficult to arrive at a definitive diagnosis. We aim to describe the most common situations that can give rise to a condition resembling overt endogenous hypercortisolism and try to answer questions that physicians often face in clinical practice. It is important to know the relative prevalence of these different situations, bearing in mind that most of the conditions generating PCS are relatively common (such as metabolic syndrome and polycystic ovary syndrome), while CS is rare in the general population. Physicians should consider CS in the presence of additional features. Appropriate treatment of underlying conditions is essential as it can reverse the hormonal abnormalities associated with PCS. Close surveillance and a thorough assessment of a patient's hormone status will ultimately orient the diagnosis and treatment options over time.